2021
DOI: 10.1371/journal.pgen.1009794
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of lrrk2 causes early developmental abnormalities and age-dependent increase of monoamine catabolism in the zebrafish brain

Abstract: LRRK2 gain-of-function is considered a major cause of Parkinson’s disease (PD) in humans. However, pathogenicity of LRRK2 loss-of-function in animal models is controversial. Here we show that deletion of the entire zebrafish lrrk2 locus elicits a pleomorphic transient brain phenotype in maternal-zygotic mutant embryos (mzLrrk2). In contrast to lrrk2, the paralog gene lrrk1 is virtually not expressed in the brain of both wild-type and mzLrrk2 fish at different developmental stages. Notably, we found reduced cat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 82 publications
(133 reference statements)
0
3
0
Order By: Relevance
“…There is a difficulty in understanding such autosomal dominant disease because it might not be clear whether a loss of the normal function of the gene is a major cause of the phenotype or whether a gain of toxic function can explain the disease. There have been several zebrafish models of Lrrk2, but we will await further evaluations and consistent findings [114][115][116][117].…”
Section: Zebrafish and Medaka Models Of Parkinson's Diseasementioning
confidence: 83%
“…There is a difficulty in understanding such autosomal dominant disease because it might not be clear whether a loss of the normal function of the gene is a major cause of the phenotype or whether a gain of toxic function can explain the disease. There have been several zebrafish models of Lrrk2, but we will await further evaluations and consistent findings [114][115][116][117].…”
Section: Zebrafish and Medaka Models Of Parkinson's Diseasementioning
confidence: 83%
“…Leucine-rich repeat kinase 2 (LRRK2) is a multidomain protein interacting with parkin [ 227 , 228 ]. The studies of knockdown or knockout of lrrk2 have reported various but conflicting phenotypes in terms of the number of dopaminergic neurons [ 204 , 205 , 206 , 207 , 208 , 209 ]. Notably, the mechanism underlying the pathogenic effect of PD by LRRK2 mutation remains unknown because point mutations have been found among different domains [ 228 ].…”
Section: Small Fish Models To Study Mitochondrial Function/dysfunctionmentioning
confidence: 99%
“…Some studies reported loss of DA neurons and locomotion defects following LRRK2 knockdown, while others showed no such effects even when the same morpholino RNAs were used (Prabhudesai et al, 2016; Ren et al, 2011; Sheng et al, 2010). Subsequently, several Lrrk2‐deficient lines were established by gene editing, yet no locomotion defect or DA neuron loss was detected (Suzzi et al, 2021; Wint & Sirotkin, 2020). In contrast, the transient overexpression of wild‐type or G2019S human LRRK2 in zebrafish resulted in impaired ubiquitin–proteasome activity (Lichtenberg et al, 2011).…”
Section: Genetic Pd Models In Zebrafishmentioning
confidence: 99%